(untitled) (Economic and Political Thought, 2013)
The article is aimed at analyzing legal and institutional conditions of contemporary Polish foreign policy. The contents were divided into four parts. After the introduction, the author analyzes the institutions responsible for the development and implementation of Polish foreign policy. The third part deals with the essence of the Polish foreign policy in the conditions of cohabitation. In the conclusions, the author points out that the institutional problems existing in the Polish foreign policy result from both inaccurate regulations in the 1997 Constitution of the Republic of Poland and personal and political features of the most important people in the state.